Morphological differentiation of Brachionus calyciflorus caused by predation and coal ash pollution. Issue 1 (December 2017) - Xue, Ying-Hao; Yang, Xiao-Xue; Zhang, Gen; Xi, Yi-Long
Abstract Different rotifer stains exhibited remarkably morphological differences which could not be eliminated under laboratory conditions. In the present study, we hypothesized that predation pressure and pollution might be two forces driving morphological differentiation of rotifer. To test this hypothesis, rotifers (Brachionus calyciflorus ) belonging to two sibling species were collected from three special lakes (with coal ash pollution, high predation pressure or neither) and cultured for more than three months to investigate their potential differentiation in morphology. Twelve morphological parameters were measured and compared among three lakes at four food density (Scenedesmus obliquus ). The results showed that most of the tested morphological parameters changed in response to food level and differed among three habitats. Rotifers from the habitat with high predation pressure evolved stable long posterior lateral spine and relatively small body size. Rotifers collected from the polluted habitat was of smaller body size, compared with those from ordinary habitat. Bigger eggs were laid by rotifers from polluted area or lake with high predation pressure, enabling newborns more resistant to pollution or predation, and thus ensuring the survival rate of newborns. Finally, we concluded that both predation and pollution could affect the morphological differentiation and evolution of rotifers.